Ammonium Ion and Structural Water Co‐Assisted Zn2+ Intercalation/De‐Intercalation in NH4V4O10∙0.28H2O†. Issue 7 (27th May 2021) - Zhu, Ting; Mai, Bo; Hu, Ping; Liu, Ziang; Cai, Congcong; Wang, Xuanpeng; Zhou, Liang
Main observation and conclusion: The cathode material plays a crucial role in the performances of aqueous zinc‐ion batteries (ZIBs). Herein, we report an ammonium vanadate (NH4 V4 O10 ∙0.28H2 O, NHVO) aqueous ZIB cathode material. The obtained NHVO microflowers manifest high discharge capacity (410 mA·h∙g –1 at 0.2 A∙g –1 ), long‐term durability (76% capacity retention over 500 cycles), as well as ideal rate performance (112 mA·h∙g –1 at 10 A∙g –1 ). The impressive electrochemical performance can be attributed to the ammonium ion and structural water co‐assisted Zn 2+ intercalation/de‐intercalation, which has been demonstrated by various ex‐situ and in‐situ characterizations. The superior electrochemical performance makes the NHVO microflower an ideal candidate cathode material for aqueous ZIBs. Abstract : As zinc ion battery cathode material, the NH4 V4 O10 ·0.28H2 O microflowers deliver a high discharge capacity (410 mA·h·g –1 at 0.2 A·g –1 ) and an ideal rate performance, which is significantly better than most vanadium‐based materials. The ex‐situ and in‐situ characterizations demonstrate the impressive electrochemical performance, which can be attributed to the ammonium ion and structural water co‐assisted Zn 2+ intercalation/de‐intercalation.